Geographical basis of tourism types in Dukan District - hmd, pshtiwan jwad; Saleh, Adnan Ali Muhammad (Sulaimani Journal for Humanities, 2026)
Tourism is recognized as a new industry nowadays and plays an important role in the national economy and securing national income. Dukan district is one of the most famous tourist areas in the Kurdistan Region, which has many principles and natural and human resources such as lakes, rivers, mountains, natural forests, religious and historical sites, etc. The aim of our research is the geographical basis of tourism types in Dukan district affected by natural and human factors. To achieve the aim of the research, we relied on descriptive, analytical and practical methods using geographical information systems Tourism, the availability of natural and human resources is the main reason for many types of tourism that can be used throughout the year and become a major factor in creating jobs and reviving the region Strengthen national products through domestic and foreign investment by building large tourism communities in important tourist areas.
Keywords: Tourism; types of tourism; natural and human resources; Dukan district